Selection Forces Driving Herding of Herbivorous Insect Larvae - Despland, Emma (Frontiers in Ecology and Evolution, 2021)
Herding behavior is widespread among herbivorous insect larvae across several orders. These larval societies represent one of several different forms of insect sociality that have historically received less attention than the well-known eusocial model but are showing us that social diversity in insects is broader than originally imagined. These alternative forms of sociality often focus attention on the ecology, rather than the genetics, of sociality. Indeed, mutually beneficial cooperation among individuals is increasingly recognized as important relative to relatedness in the evolution of sociality, and I will explore its role in larval insect herds. Larval herds vary in in the complexity of their social behavior but what they have in common includes exhibiting specialized social behaviors that are ineffective in isolated individuals but mutually beneficial in groups. They hence constitute cooperation with direct advantages that doesn’t require kinship between cooperators to be adaptive. Examples include: trail following, head-to-tail processions and other behaviors that keep groups together, huddling tightly to bask, synchronized biting and edge-feeding to overwhelm plant defenses, silk production for shelter building or covering plant trichomes and collective defensive behaviors like head-swaying. Various selective advantages to group living have been suggested and I propose that different benefits are at play in different taxa where herding has evolved independently. Proposed benefits include those relative to selection pressure from abiotic factors (e.g., thermoregulation), to bottom-up pressures from plants or to top-down pressures from natural enemies. The adaptive value of herding cooperation must be understood in the context of the organism’s niche and suite of traits. I propose several such suites in herbivorous larvae that occupy different niches. First, some herds aggregate to thermoregulate collectively, particularly in early spring feeders of the temperate zone. Second, other species aggregate to overwhelm host plant defenses, frequently observed in tropical species. Third, species that feed on toxic plants can aggregate to enhance the warning signal produced by aposematic coloration or stereotyped defensive behaviors. Finally, the combination of traits including gregariousness, conspicuous behavior and warning signals can be favored by a synergy between bottom-up and top-down selective forces. When larvae on toxic plants aggregate to overcome plant defenses, this grouping makes them conspicuous to predators and favors warning signals. I thus conclude that a single explanation is not sufficient for the broad range of herding behaviors that occurs in phylogenetically diverse insect larvae in different environments.